Phase transition in a cell fluid model - Kozlovskii, M.P.; Dobush, O.A. (Condensed Matter Physics, 2017)
We propose a method of describing a phase transition in a cell fluid model with pair interaction potential that
includes repulsive and attractive parts. An exact representation of the grand partition function of this model is
obtained in the collective variables set. The behavior of the system at temperatures below and above the critical
one is explored in the approximation of a mean-field type. An explicit analytic form of the equation of state
which is applicable in a wide range of temperatures is derived, taking into account an equation between chemical potential and density. The coexistence curve, the surface of the equation of state and the phase diagram of
the cell Morse fluid are plotted. Запропоновано метод опису фазового переходу в комiрковiй моделi плину iз парним потенцiалом взаємодiї, що мiстить частини вiдштовхування i притягання. Отримано точне представлення великої статистичної суми цiєї моделi в формалiзмi колективних змiнних. У наближеннi типу молекулярного поля
дослiджено поведiнку системи при температурах вищих i нижчих, нiж критична. Використовуючи рiвняння, що зв’язує хiмiчний потенцiал та густину, розраховано явну аналiтичну форму рiвняння стану, що
справедливе для широкої областi температур. Представлено криву спiвiснування, поверхню рiвняння
стану та дiаграму стану комiркового плину Морзе.